Evidence-based Perioperative Management: Strategic Shifts in Times of Fast Track Surgery - COPRA, Sascha Santosh; SCHMIDT, Sven Christian; FOTOPOULOU, Christina; SEHOULI, Jalid; SCHUMACHER, Guido (Anticancer research, 2009)
Changes in perioperative management is an ever evolving subject. The primary aim is to improve patient care and more recently to increase economic efficacy. Data from various randomized studies have caused a shift from traditional care concepts towards evidence based multimodal treatment strategies. They may lead to dramatic changes in perioperative patient care such as the routine use of nasogastric decompression, mechanical bowel preparation and established nutrition schemes. Further aspects of modern perioperative patient care include epidural analgesia, antibiotic prophylaxis, intraoperative fluid management and early mobilization. It has been generally accepted that these multimodal treatment concepts also known as âfast track surgeryâ show no differences in patient morbidity while significantly reducing patient discomfort and duration of hospitalization. However, despite the evidence-based superiority, widespread implementation has not yet occurred. The aim of this review is to highlight and discuss current changes and to show future perspectives of perioperative treatment strategies.